Production of Furfural from Corncobs Agricultural Waste by Acid Hydrolysis at Atmospheric Pressure (Universitas Negeri Semarang, 2014)
Corncob is the renewable agricultural biomass which has great potency to be developed into useful chemical. It can be used as raw material for producing furfural as it contains high concentration of pentosan up to 32%. Furfural is a useful chemical intermediate which may be further processed into other valuable products, such as furan, furoic acid, and furfuryl alcohol. Furfural is also an important chemical solvent. The aim of this research was to optimize the production process and maximize the yield of furfural. The research was conducted in three steps which included pretreatment of raw material, hydrolysis, and distillation. Corncobs was ground to form powder with a maximum particle size of 150 mesh and then hydrolysed in a stirred reactor using H2SO4 at temperature variation of 80oC, 90oC, and 100oC for 2 hr, 3 hr, and 4 hr at atmospheric pressure. The hydrolysate was filtrated and the filtrate was added by toluene and being kept for 12 hours. The product was separated by distillation at 110oC. The result showed the highest yield of furfural from corncobs was 31% which obtained by acid hydrolysis at 100oC for 4 hours. Analysis using GC-MS identified furfural in the product and several impurities, such as toluene, 1,5-heptadien-3-yne, and benzaldehyde.